Physicochemical properties, degradation kinetics, and antioxidant capacity of aqueous anthocyanin-based extracts from purple carrots compared to synthetic and natural food colorants - Perez, María Belén (2022)
As a mans to evaluate the potential of carrot anthocyanins as food colorants and nutraceutical agents, we investigated the physicochemical stability and antioxidant capacity of purple carrot extracts under different pH (2.5-7.0) and temperature (4-40 °C) conditions, in comparison to a commercial synthetic (E131) and a natural grape-based (GRP) colorant. During incubation, the colorants were weekly-monitored for various color parameters, concentration of anthocyanins and phenolics, and antioxidant capacity. Carrot colorants were more stable than GRP; and their thermal stability was equal (at 4°C) or higher than that of E131 (at 25-40°C). Carrot anthocyanins had lower degradation rate at low pH and temperature, with acylated anthocyanins (AA) being significantly more stable than non-acylated anthocyanins (NAA). Anthocyanins acylated with feruloyl and coumaroyl glycosides were the most stable carrot pigments. The higher stability of carrot colorants is likely due to their richness in AA and –to a lesser extent- copigmentation with other phenolics.